Analysis of the risk difference in post-spinal anesthesia hypotension between primiparas and multiparas in cesarean section - Zhang, Jizheng; Che, Jinli; Sun, Xiaohua; Li, Yi; Ren, Wanlu (Frontiers in Surgery, 2025)
IntroductionThis study aimed to investigate the impact of maternal type and its interactions on the incidence of hypotension following spinal anesthesia.MethodsIn this retrospective cohort study, both primiparous and multiparous women were included. Demographic, pregnancy-related, and hemodynamic data were collected. Univariate and multivariate logistic regression analyses were performed to evaluate the association between these factors and the occurrence of hypotension after spinal anesthesia. Additionally, multivariate models with and without maternal type were constructed, followed by interaction analysis.ResultsPrimiparous women had a lower median age and slightly greater weight gain during pregnancy compared to multiparous women. They also exhibited significantly higher pleth variability index (PVI) and heart rate (HR), while heart rate variability (HRV) was significantly lower. Univariate regression analysis identified maternal type, age, weight gain during pregnancy, estimated fetal weight, PVI, HR, HRV, and systolic blood pressure (SBP) as significant predictors of hypotension. Multivariate model analysis showed that adding the variable of parity significantly improved the model’s ability to discriminate the occurrence of hypotension (Model 2 AUC = 0.815 vs. Model 1 AUC = 0.740). Interaction analysis revealed significant interactions between heart rate variability (HRV), systolic blood pressure (SBP), gestational weight gain, and parity, suggesting that these physiological characteristics are more strongly associated with hypotension in primiparas.DiscussionIn conclusion, primiparous women are at significantly higher risk of developing hypotension after spinal anesthesia than multiparous women. Baseline perfusion index (PI), estimated fetal weight, and baseline PVI are key contributing factors to this outcome.